Comparison between radiochromic film and Sun nuclear edge diode detector during the commissioning of small field size radiosurgery cones - Thiago Schmeling Fontana; Karen Pieri Bueno; Lucas Delbem Albino; Ernesto Henrique Roesler; Matheus Fernando dos Santos; Viviane Khoury Asfora; Helen Jamil Khoury (Brazilian Journal of Radiation Sciences)
Stereotactic Radiosurgery (SRS) is a procedure that uses ionizing radiation in a single fraction or few fractions to treat intracranial lesions. Usually, for these treatments, small photon fields, formed by circular collimators or micro multileaf collimators are used. The objective of the present work is to compare the measurements of the dose in depth (PDD), the off-axis ratio (OAR), and the output factor (OF) using Edge diode and radiochromic films and analyzing the agreement between the two detectors during these measures. In the gamma index analysis of the profiles, the minimum percentage reached was 98.3% of the points in the criterion 1% and 0.5 mm. The maximum percentage difference in the output factor was 2.79% for a cone 4 mm and 10FFF. In the gamma index analysis of the PDDs, the minimum percentage reached was 97% of the points in the criterion 1% and 1mm. The results show a good agreement between the edge detector and the film in small field measurements for radiosurgery.